The Effectiveness of the Ethnochemistry-based Problem Based Learning Model on Students' Problem-Solving Ability in Chemistry Learning: A Meta-analysis Study in 2021-2024 - Hotmauli Gultom; Eli Rohaeti (Postgraduate, University of Mataram, 2024)
This research is based on many ethnoscience-based problem-based learning studies on students' problem-solving skills. However, many different studies are related to drawing conclusions regarding the application of ethnochemistry-based project-based learning to students' problem-solving skills. This study aims to analyze the influence of ethnochemistry-based problem-based learning model on students' problem-solving ability in chemistry learning. Compared to conventional models. This research is a type of meta-analysis research. Data collection techniques through google scholar database searching; ERIC; ScienceDirect; Wiley; and IEEE. The research data was analyzed to calculate the effect size value of 17 primary studies that met the inclusion criteria. Data analysis with the help of JSAP 0.16.3 software. The results of this study concluded that the ethnochemistry-based problem-based learning model had a significant influence on students' problem-solving ability with an mean effect size ( d = 0.997; p < 0.001) including the high effect size category. These findings conclude that the ethnochemistry-based problem-based learning model is effective in improving students' problem-solving skills compared to conventional learning models. The results of the meta-analysis provide more accurate information so that it can improve the quality of chemistry learning for students at school.